KARAKTERISTIK FISIKOKIMIA PATI SAGU HASIL PENGERINGAN SECARA FLUIDISASI MENGGUNAKAN ALAT PENGERING CROSS FLOW FLUIDIZED BED BERTENAGA SURYA DAN BIOMASSA - Abadi Jading; Eduard Tethool; Paulus Payung; Sarman Gultom (Dept. of Chemical Engineering, Diponegoro University, 2011)
PHYSICOCHEMICAL CHARACTERISTICS OF SAGO STARCH OBTAINED FROM FLUIDIZED BED DRYING USING SOLAR AND BIOMASS POWERED CROSS FLOW FLUIDIZED BED DRYER. The research aim is to study the comparative quality of sago starch drying results using cross flow fluidized bed dryer powered by solar and biomass in conventional drying, particularly the chemical composition and physicochemical characteristics. This research was conducted through a drying phase of wet sago starch using a cross flow fluidized bed dryer, and drying in conventional as well as dried sago starch quality testing results are drying. The results of this study indicate that dry sago starch which has been drained by means of cross flow fluidized bed dryer has a chemical composition that does not vary much with starch which is dried by conventional drying, so that the dried sago starch produced by the dryer is very good. On the other hand the use of dryers is the more correct because the physicochemical properties of sago starch using a low drying temperature and drying time is short. Tujuan penelitian ini adalah mempelajari perbandingan kualitas pati sagu hasil pengeringan menggunakan alat pengering cross flow fluidized bed bertenaga surya dan biomassa dengan pengeringan secara konvensional, khususnya komposisi kimia dan karakteristik fisikokimia. Penelitian ini dilakukan melalui beberapa tahapan yaitu pengeringan pati sagu basah menggunakan alat pengering cross flow fluidized bed, pengeringan secara konvensional serta pengujian kualitas pati sagu kering hasil pengeringan. Hasil dari penelitian ini menunjukkan bahwa pati sagu kering yang telah dikeringkan dengan alat pengering cross flow fluidized bed memiliki komposisi kimia yang tidak berbeda jauh dengan pati yang dikeringkan dengan cara pengeringan secara konvensional, sehingga pati sagu kering yang dihasilkan oleh alat pengering tersebut sangat baik. Di sisi lain penggunaan alat pengering ini semakin memperbaiki sifat fisikokimia pati sagu sebab menggunakan suhu pengeringan yang rendah dan waktu pengeringan yang singkat. Kata Kunci: pengering unggun terfluidakan; fisikokimia; pati sagu